Effect of mechanically aged minimalist and traditional footwear on female running biomechanics. (September 2019) - Lippa, Nadine; Bonacci, Jason; Collins, Paul K; Rawlins, James W; Gould, Trenton E
The purpose of this study was to improve the understanding of human–material interactions by combining polymer engineering and biomechanical approaches. The forefoot and heel of traditional shoes and minimalist running shoes were degraded using a mechanical aging protocol to quantify (1) the effect of subject-specific degradation and (2) human biomechanical effects due to decreased material properties. Four recreational-level female participants ran in the shoes pre-mechanical aging to determine the aging protocol input parameters and post-mechanical aging to evaluate the effect of degradation on kinematics and kinetics. Initial biomechanics translated into different mechanical aging input parameters among conditions: 500 greater number of impact cycles for minimalist shoe, 430 N higher peak force for forefoot, 75 kPa greater peak stress for the heel, 3.1 and 13.7 kN/s greater loading rates for minimalist shoe and the heel, and recovery time 220 ms greater for the heel. From mechanical aging, the shoe types and regions lost 1.2–1.8 mm thickness and 38%–54% energy absorption overall, while drop decreased 0.6 mm for traditional shoe only. Samples degraded at different rates depending on runner-specific input parameters. Human kinematics and kinetics were affected by both shoe type and aging. Aging of the shoes decreased knee flexion velocity (1°/s; p  = 0.01), decreased ankle dorsiflexion during stance (3°, p  = 0.01), and increased the vertical loading rate (4 BW/s, p  = 0.01). The results support previous findings that different footwear influence running biomechanics and concurrently advance footwear science to show running biomechanics are also influenced by shoe degradation rates, such that unique and intuitive human–material interactions are apparent.